To complete the table of values for the function \( y = x^3 + 4 \), we can calculate the value of \( y \) for each given \( x \).
-
For \( x = -3 \): \[ y = (-3)^3 + 4 = -27 + 4 = -23 \]
-
For \( x = -2 \): \[ y = (-2)^3 + 4 = -8 + 4 = -4 \]
-
For \( x = -1 \): \[ y = (-1)^3 + 4 = -1 + 4 = 3 \]
-
For \( x = 0 \): \[ y = (0)^3 + 4 = 0 + 4 = 4 \]
-
For \( x = 1 \): \[ y = (1)^3 + 4 = 1 + 4 = 5 \]
-
For \( x = 2 \): \[ y = (2)^3 + 4 = 8 + 4 = 12 \]
-
For \( x = 3 \): \[ y = (3)^3 + 4 = 27 + 4 = 31 \]
Now, we can fill in the completed table with the calculated values:
\[ \begin{array}{|c|c|} \hline x & y \ \hline -3 & -23 \ -2 & -4 \ -1 & 3 \ 0 & 4 \ 1 & 5 \ 2 & 12 \ 3 & 31 \ \hline \end{array} \]